Adaptive Gain and Analog Wavelet Transform for Low-Power Infrared Image Sensors - P. Villard; T. Thabuis; M. Belleville; G. Sicard; G. Decaens; M. Zecri (Active and Passive Electronic Components)
A decorrelation and analog-to-digital conversion scheme aiming to reduce the power consumption of infrared image sensors is presented in this paper. To exploit both intraframe redundancy and inherent photon shot noise characteristics, a column based 1D Haar analog wavelet transform combined with variable gain amplification prior to A/D conversion is used. This allows to use only an 11-bit ADC, instead of a 13-bit one, and to save 15% of data transfer. An 8×16 pixels test circuit demonstrates this functionality.